Pendekatan Feminis terhadap Narasi 2 Samuel 13:1-39 dan Implikasinya terhadap Kekerasan Seksual di Lingkungan Keluarga - Liandra Yolanda Camerling; Alelen Darmas Singerin (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
Sexual violence can occur in any environment, including the family. Most victims of sexual violence are women. One narrative depicting violence in a family context is the story of Tamar and Amnon in 2 Samuel 13:1-39, which is part of King David’s family history. The family, which should be a place of refuge, instead becomes an unsafe place. The patriarchal system that gives power to men and places women in a subordinate position is one of the causes. The text of 2 Samuel 13:1-39 is implied in the modern context because the problem of sexual violence in private spaces such as the home is also experienced by women today. A feminist approach is used to draw out women’s values and analyze the structure of the Davidic Kingdom family, identifying the causes and impacts, and how Tamar, as a woman, faced and overcame the moral crisis and sexual violence she experienced. This study uses a qualitative descriptive method with a hermeneutic approach, focusing on literature review to discuss related topics. The author found that Tamar, who experienced sexual violence in the family environment, did not receive justice. The cause of violence is the patriarchal system.  Power struggles and invalid laws. Tamar did not remain silent but sought justice for herself by communicating her experiences to the public through religious and social symbolism. Learning from Tamar teaches modern women how to speak out about the injustices they experience.